Wind Structure of a Subtropical Squall Line in China: Results from Dual-Doppler Radar Data - Haiguang Zhou (Advances in Meteorology)
A subtropical squall line moved from Guangxi to Guangdong province in South China on 23-24 April 2007, which resulted in gale and heavy precipitation. The three-dimensional (3D) wind field of the squall line in its mature period was retrieved by Guangzhou-Shenzhen dual-Doppler data. The 3D conceptual model of this squall line was proposed. On the horizontal plane, the storm-relative front-to-rear inflow prevailed at the lower altitudes of the leading edge. The rear-to-front cold inflow in the stratiform region was observed below 3 km height, which enhanced the convergence in the convective region. At the middle altitudes of the squall line, the front-to-rear horizontal flow prevailed. Strong updrafts were observed at the lower and middle altitudes of the leading edge. Some convergence centers were located at the lower altitudes of the convective region. Furthermore, the storm-relative flow in the vertical cross-section perpendicular to the squall line was revealed. The front-to-rear warm flow extended from the surface to 7.5 km altitude at the leading edge. Above it, part of the front-to-rear inflow blew upward and then forward, and the other part of the inflow blew backward. The descending rear-to-front cold flow was only seen below 3 km height in the stratiform region.